(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article covers the issues of effective use of modern pedagogical software tools in the course of the lesson. The widespread introduction of information and communication technologies in the educational process creates a great opportunity for the development of students’ knowledge, skills and abilities. The use of multimedia tools, interactive platforms, electronic educational resources and simulation programs in the course of the lesson increases the interest of students and ensures the efficiency of learning. This article is devoted to the study of the importance of modern pedagogical technologies, their methods of application and their impact on the educational process. According to the results of the research, it was found that the use of modern tools helps to improve the quality of education and the work efficiency of teachers. At the same time, the article contains recommendations on the selection and use of pedagogical software tools.